2017
DOI: 10.19044/esj.2017.v13n33p11
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapy and Functional Motor Recovery in Patient with Guillain-Barré Syndrome - Case Report

Abstract: Introduction: Guillain-Barré syndrome (GBS) is an autoimmune disease with sudden onset and progressive impairment of the peripheral nerves. Aim: To study the influence of applied physical therapy (PT) on functional recovery in patient with a prolonged complicated course of GBS, Landry ascending paralysis and assisted breathing and 4 months in-hospital stay. Case report: The study was conducted with a 34-year-old woman in subacute stage of GBS, over the course of 2 months in the patient's home, after discharge.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…21,22 The physical therapy program improved lower limb muscle power in this study similar to the previous study by Fisher et al 23 Besides, the results showed improved muscle power in lower limbs, improved static and dynamic balance in sitting, and functional status. Resistance training in this study achieved similar results among AMSAN patients, which has been previously reported by Markvardsen et al and Dimitrova et al 24,25 However, COVID-19 appears to be uncommon with GBS26, few cases has been reported in previous studies and recommends COVID test for GBS patients .27, 28 It was reported that COVID-19 will further reduce the functional ability of GBS patients. 29 Thus, physiotherapy at early stages of COVID-19 management will facilitate recovery30 and it is also noted that the physical exercise along with the pharmacological treatment influenced the Blood pressure levels, Oxygen saturation, Respiratory rate, and pulse rate.…”
Section: Discussionsupporting
confidence: 85%
“…21,22 The physical therapy program improved lower limb muscle power in this study similar to the previous study by Fisher et al 23 Besides, the results showed improved muscle power in lower limbs, improved static and dynamic balance in sitting, and functional status. Resistance training in this study achieved similar results among AMSAN patients, which has been previously reported by Markvardsen et al and Dimitrova et al 24,25 However, COVID-19 appears to be uncommon with GBS26, few cases has been reported in previous studies and recommends COVID test for GBS patients .27, 28 It was reported that COVID-19 will further reduce the functional ability of GBS patients. 29 Thus, physiotherapy at early stages of COVID-19 management will facilitate recovery30 and it is also noted that the physical exercise along with the pharmacological treatment influenced the Blood pressure levels, Oxygen saturation, Respiratory rate, and pulse rate.…”
Section: Discussionsupporting
confidence: 85%
“…Residual neuromuscular deficiency, observed in the continued aftermath of GBS (Davidson et al, 2009(Davidson et al, , 2010Stockley et al, 2013), necessitates change in movement strategy placing new burdens on body biomechanics (Dimitrova et al, 2017). Alterations to biomechanics may, over time, result in musculoskeletal disorders causing specific anatomical lesions and non-specific, general pain.…”
Section: Demographicmentioning
confidence: 99%